Muscle wasting and function after muscle activation and early protocol‐based physiotherapy: an explorative trial. Issue 4 (23rd April 2019) - Wollersheim, Tobias; Grunow, Julius J.; Carbon, Niklas M.; Haas, Kurt; Malleike, Johannes; Ramme, Sara F.; Schneider, Joanna; Spies, Claudia D.; Märdian, Sven; Mai, Knut; Spuler, Simone; Fielitz, Jens; et al.
Abstract: Background: Early mobilization improves physical independency of critically ill patients at hospital discharge in a general intensive care unit (ICU)‐cohort. We aimed to investigate clinical and molecular benefits or detriments of early mobilization and muscle activating measures in a high‐risk ICU‐acquired weakness cohort. Methods: Fifty patients with a SOFA score ≥9 within 72 h after ICU admission were randomized to muscle activating measures such as neuromuscular electrical stimulation or whole‐body vibration in addition to early protocol‐based physiotherapy (intervention) or early protocol‐based physiotherapy alone (control). Muscle strength and function were assessed by Medical Research Council (MRC) score, handgrip strength and Functional Independence Measure at first awakening, ICU discharge, and 12 month follow‐up. Patients underwent open surgical muscle biopsy on day 15. We investigated the impact of muscle activating measures in addition to early protocol‐based physiotherapy on muscle strength and function as well as on muscle wasting, morphology, and homeostasis in patients with sepsis and ICU‐acquired weakness. We compared the data with patients treated with common physiotherapeutic practice (CPP) earlier. Results: ICU‐acquired weakness occurs within the entire cohort, and muscle activating measures did not improve muscle strength or function at first awakening (MRC median [IQR]: CPP 3.3 [3.0–4.3]; control 3.0 [2.7–3.4]; intervention 3.0 [2.1–3.8]; P > 0.05 for all), ICU discharge (MRC median [IQR]: CPP 3.8 [3.4–4.4]; control 3.9 [3.3–4.0]; intervention 3.6 [2.8–4.0]; P > 0.05 for all), and 12 month follow‐up (MRC median [IQR]: control 5.0 [4.3–5.0]; intervention 4.8 [4.3–5.0]; P = 0.342 for all). No signs of necrosis or inflammatory infiltration were present in the histological analysis. Myocyte cross‐sectional area in the intervention group was significantly larger in comparison with the control group (type I +10%; type IIa +13%; type IIb +3%; P < 0.001 for all) and CPP (type I +36%; type IIa +49%; type IIb +65%; P < 0.001 for all). This increase was accompanied by an up‐regulated gene expression for myosin heavy chains (fold change median [IQR]: MYH1 2.3 [1.1–2.7]; MYH2 0.7 [0.2–1.8]; MYH4 5.1 [2.2–15.3]) and an unaffected gene expression for TRIM63, TRIM62, and FBXO32 . Conclusions: In our patients with sepsis syndrome at high risk for ICU‐acquired weakness muscle activating measures in addition to early protocol‐based physiotherapy did not improve muscle strength or function at first awakening, ICU discharge, or 12 month follow‐up. Yet it prevented muscle atrophy.